Perangkat Pembelajaran Mata Kuliah Kapita Selekta Matematika SMP Terintegrasi Nilai Islam - Nurmitasari, Nurmitasari; Noerhasmalina, Noerhasmalina; Hidayatullah, Kholid (Universitas Muhammadiyah Kotabumi, 2025)
To produce graduates with new literacy skills, such as data literacy, technology literacy, and human literacy, combined with noble character, precise learning planning is essential. One such plan is the Semester Program Plan (RPS) integrated with Islamic values, aligning with the needs of Industry 4.0 graduates and the vision of the study program, faculty, and university. This study aims to develop an Islamic-integrated RPS that is feasible and effective for the Selected Topics in Junior High School Mathematics course. The research subjects were first-semester students of the Mathematics Education Study Program, Faculty of Teacher Training and Education (FKIP), Universitas Muhammadiyah Pringsewu Lampung, for the 2024/2025 academic year. The research employed the 4-D development model (Define, Design, Develop, Disseminate) by Thiagarajan. Data collection techniques included expert assessment sheets, observation sheets for learning implementation and student activities, student response questionnaires, and learning outcome tests. Data analysis was conducted using average scores and percentages. The findings of this study include four stages. In the define stage, data revealed that the characteristics of students include being closer to peers for sharing ideas and providing mutual support, being independent, and having a high curiosity about technological advancements. In the design stage, an RPS integrated with Islamic values was developed. In the develop stage, a feasible and effective RPS was obtained. In the disseminate stage, the RPS was used by the course instructor. With a feasible and effective learning tool integrated with Islamic values, it can enhance students' academic achievement and character development.